Arqueoantrossolos do Pantanal Sul-Mato-Grossense - Rosa, Gabriel Palucci (2022)
The present work was carried out in the vegetated mounds and paleo-levees in the Pantanal landscape of the Rio Negro region (SIRN) in the Pantanal sul-mato-grossense region. With the objective of understanding the influence of human occupation on soil genesis, chemical and physical analyses, X-ray diffraction (XRD), total content analysis in TFSA, microscopic and microchemical analyses were performed. In terms of physical aspects, the fine sand fraction stood out in most horizons. The shell layers found in the profiles, similar to shell mounds, showed positive and low correlations with indicators of human occupation, such as P content, when analyzing the profiles as a whole. The levels of Mn, Cu, Zn, P, Sr and Ba, used as geochemical indicators of prehistoric anthropic action, presented high values, allowing classification as Anthrosols by FAO and anthropic horizons by SiBCS. The P content extracted by Mehlich-1 reached values higher than 3,000 mg.kg-1, similar to those evidenced in Indian black earth and coastal shell mound profiles. XRD analysis identified the presence of kaolinite, apatite and illite in the clay fraction. From the images obtained by SEM-EDS and petrographic microscope, it was possible to identify that the coarse fraction is composed of rounded quartz, as well as fragments of shells and bones, while the fine fraction stands out for being rich in Ca2+ and Mg2+. Thus, anthropic action was verified in the genesis of soil in the highest segments of the landscape.